Arterial thrombosis in Philadelphia-negative myeloproliferative neoplasms predicts second cancer: a case-control study - De Stefano, Valerio; Ghirardi, Arianna; Masciulli, Arianna; Carobbio, Alessandra; Palandri, Francesca; Vianelli, Nicola; Rossi, Elena; Betti, Silvia; Di Veroli, Ambra; Iurlo, Alessandra; Cattaneo, Daniele; Finazzi, Guido; et al. (Blood, 2020)
Patients with Philadelphia-negative myeloproliferative neoplasm (MPN) are prone to the development of second cancers, but the factors associated with these events have been poorly explored. In an international nested case-control study, we recruited 647 patients with carcinoma, nonmelanoma skin cancer, hematological second cancer, and melanoma diagnosed concurrently or after MPN diagnosis. Up to 3 control patients without a history of cancer and matched with each case for center, sex, age at MPN diagnosis, date of diagnosis, and MPN disease duration were included (n = 1234). Cases were comparable to controls for MPN type, driver mutations and cardiovascular risk factors. The frequency of thrombosis preceding MPN was similar for cases and controls (P = .462). Thrombotic events after MPN and before second cancer were higher in cases than in controls (11.6% vs 8.1%; P = .013), because of a higher proportion of arterial thromboses (6.2% vs 3.7%; P = .015). After adjustment for confounders, the occurrence of arterial thrombosis remained independently associated with the risk of carcinoma (odds ratio, 1.97; 95% confidence interval, 1.14-3.41), suggesting that MPN patients experiencing arterial events after MPN diagnosis deserve careful clinical surveillance for early detection of carcinoma. This study was registered at www.clinicaltrials.gov as NCT03745378.
Keywords: Kaplan-Meier Estimate; sekundární malignity; myeloproliferativní poruchy; multivariační analýza; Kaplanův-Meierův odhad; Multivariate Analysis; lidé; trombóza; Philadelphia Chromosome; filadelfský chromozom; studie případů a kontrol; následné studie; Myeloproliferative Disorders; Neoplasms, Second Primary; Arteries; Follow-Up Studies; Case-Control Studies; Thrombosis; arterie; Humans